Intussusception associated with bacterial meningitis. Issue 1 (1st July 2001) - Crushell, E; Flanagan, O; Devins, M; Dunne, K; Gleeson, J
Abstract : Despite its common association with viral illnesses, intussusception has only rarely been found in the presence of bacterial infections. Two infants are described, both of whom were admitted to hospital with bilious vomiting, drowsiness, and dehydration. Both infants required urgent intravenous volume expansion. Intussusception was confirmed, and reduction was achieved by enema in both cases. Recovery was slow, and one infant developed a seizure. Evidence of meningococcal meningitis was found in both, with septicaemia in one. Neurological outcome is normal to date, and there has been no recurrence of intussusception in either case.